Penerapan Model Project Based Learning untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V SDN Sawah Besar 01 - Saroh, Mu’asaroh; Filia Prima Atharina; Mira Azizah; Diah Saraswati (JURNAL FEMBOY BOOL RAPET, 2025)
This study aims to improve the learning outcomes of fifth-grade students at SDN Sawah Besar 01 in the subject of Integrated Science and Social Studies (IPAS) through the application of the Project Based Learning (PjBL) model. The research employed Classroom Action Research (CAR) across two cycles. In the first cycle, students created models of the human digestive system; in the second cycle, they conducted simple experiments to test carbohydrate content and developed a food pyramid project. Data were collected through observation and learning outcome tests, then analyzed both quantitatively and qualitatively. The results showed a significant improvement in students’ learning outcomes, with the average score increasing from 45.93 (pre-cycle) to 66.30 (cycle I), and further to 84.63 (cycle II). The PjBL model proved effective in enhancing student engagement, conceptual understanding, and critical and collaborative thinking skills in IPAS learning.